Analisis Implementasi Pasal 183 KHI tentang Pembagian Harta Waris di Desa Pasuruhan Kidul Kecamatan Jati Kabupaten Kudus - Abdul Haris Naim; Ahmad Safi'i (Program Studi Hukum Keluarga Islam, 2021)
Inheritance has been regulated in the Al-Quran and As-Sunnah, but there are still some people who do not understand it, causing many problems that are not by the rules that have been set. In Article 183 of the KHI, it is stated that the distribution of inheritance is said to be legal and permissible if all families agree to settle it amicably or by peaceful means. This is done by the Pasuruan Kidul Village Community in the distribution of inheritance based on a mutual agreement. There are two formulations of the problem, namely: How is the practice of distributing community inheritance, How is Islamic law reviewing the practice of dividing community inheritance. The research approach used is descriptive qualitative. The conclusions are 1) The practice of distributing community inheritance in Pasuruan Kidul Village is carried out using the customary law system which is given equally between men and women, there is no difference in the share; 2) The distribution of the inheritance of the Pasuruan Kidul Village community deviates from the provisions of the Compilation of Islamic Law contained in the rules of Article 176 and the Qur'an Surah An-Nisa verse 11. However, based on other aspects, the practice of dividing the inheritance of the Pasuruan Kidul Village community is carried out by an equal distribution system to avoid disputes between families, namely following the provisions of customary law, it is by Article 183 KHI: